Cover Feature: Planar‐Chiral Ferrocene‐Based N‐Heterocyclic Carbene Ligands (Chem. Eur. J. 70/2018). Issue 70 (26th November 2018) - Yoshida, Kazuhiro; Yasue, Risa
Abstract : Ferrocene, a prototypical sandwich compound, has attracted the attention of many chemists since its discovery. The application of its unique structure as a ligand scaffold in transition‐metal catalysis is one of the successful examples of ferrocene chemistry. N‐heterocyclic carbene (NHC) ligands, which have characteristics different from phosphine ligands, have emerged to become an indispensable tool in coordination chemistry. What kind of ligand could be generated by combining ferrocene and NHC structures? Focusing on planar‐chiral ligands, this article summarizes advances in the field, which started at the beginning of the century. More information can be found in the Minireview by K. Yoshida and R. Yasue onpage 18575 .